Tamil Catholic literary tradition of Sri Lanka - Pilendran, Gnanamuthu Victor (Thirunelvely, Jaffna, Sri Lanka : Catholic Students' Union, 1998)
Includes bibliographical references (v. 1, p. 167-177).
Includes passages in Tamil.
Keywords: Christian literature, Tamil -- Sri Lanka; Christianity and literature -- Sri Lanka